Pengaruh Program Pendidikan dan Pelatihan Terhadap Prestasi Kerja Pegawai di Pusdiklat Ir. H. Djuanda PT. KAI Persero Bandung - Eri Sopyanti Herlina; D. Deni Koswara; Dedy Achmad Kurniady (Jurnal Tata Kelola Pendidikan, 2019)
This study entitled "The Effect of Education and Training Program Against Job Performance Employees at Pusdiklat Ir. H. Juanda PT.KAI (Persero) Bandung ". Issues examined in this study concerning the education and training programs and their influence on job performance of employees at the Training Center Ir. H. Juanda PT.KAI (Persero) Bandung with the object of study participantsTraining.Generally, this study aims to find out and get a picture of the influence of education and training programs at the Training Center Ir. H. Juanda PT.KAI (Persero) Bandung. This research uses descriptive method with quantitative approach. The data collection technique was conducted by questionnaire enclosed, with a sample of 30 participants that education and training education and training in the period from May 2016. Analysis of the calculations in this study using a support program Microsoft Excel 2007 and SPSS for Windows version 23.0.Based on calculations using the formula Weight Means Score (WMS), an overview of variable X (Education and Training) that are in the very good category with an average score of 4:06. While the general description of the variable Y (Job Performance) in the excellent category, with an average score of 424. Correlation variables X and Y have a significant relationship. It can be seen from the results of the correlation coefficient of 0.650 which is in a strong and significant category, with a coefficient of determination of 38% as well as the results of the regression analysis is Y = 0.518 + 75,201 that are significant and linear.Conclusion The study says education and training programs have a significant effect on the performance of employees in Pusdiklat Ir. H. Juanda PT.KAI (Persero) Bandung.